2018
DOI: 10.1002/eap.1714
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater wetlands can function as ecological traps for urban frogs

Abstract: Around cities, natural wetlands are rapidly being destroyed and replaced with wetlands constructed to treat stormwater. Although the intended purpose of these wetlands is to manage urban stormwater, they are inhabited by wildlife that might be exposed to contaminants. These effects will be exacerbated if animals are unable to differentiate between stormwater treatment wetlands of varying quality and some function as "ecological traps" (i.e., habitats that animals prefer despite fitness being lower than in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 60 publications
(100 reference statements)
2
46
0
Order By: Relevance
“…To our knowledge, this is the first demonstration of an ecological trap for a freshwater fish, although they have been hypothesized to form previously (Pelicice andAgostinho 2008, Jeffres andMoyle 2012). For example, traps for birds are often caused by predation (Ekroos et al 2012), whereas aquatic species might be more susceptible to traps that arise in other ways, such as the effects of stormwater pollution on frogs (Sievers et al 2018b). For example, traps for birds are often caused by predation (Ekroos et al 2012), whereas aquatic species might be more susceptible to traps that arise in other ways, such as the effects of stormwater pollution on frogs (Sievers et al 2018b).…”
Section: Managing Ecological Trapsmentioning
confidence: 84%
“…To our knowledge, this is the first demonstration of an ecological trap for a freshwater fish, although they have been hypothesized to form previously (Pelicice andAgostinho 2008, Jeffres andMoyle 2012). For example, traps for birds are often caused by predation (Ekroos et al 2012), whereas aquatic species might be more susceptible to traps that arise in other ways, such as the effects of stormwater pollution on frogs (Sievers et al 2018b). For example, traps for birds are often caused by predation (Ekroos et al 2012), whereas aquatic species might be more susceptible to traps that arise in other ways, such as the effects of stormwater pollution on frogs (Sievers et al 2018b).…”
Section: Managing Ecological Trapsmentioning
confidence: 84%
“…In (b), Cha = Chandler, Che = Cheltenham, Lyn = Lynbrook, Woo = Woodlands. Chandler and Cheltenham are two more polluted sites that have been shown to be ecological traps for spotted marsh frog Lynodynastes tasmaniensis when compared to Lynbrook and Woodlands, with the number in parenthesis showing the heavy metal quotient at each site (Sievers, Parris, Swearer, et al, ), which is an integrative measure of likely pollutant levels. In (c), black and gray circles indicate data from 2016 and 2017, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results have also shown that larvae reared in sediments from these sites had high (85%–100%) and comparable survival (K. Jeppe unpublished data). The two more polluted sites here are ecological traps for native frogs (Sievers, Parris, Hale, & Swearer, ). The traits and behaviors of animals likely to increase susceptibility to ecological traps have been described, for example, slow rate of evolution, slow generation time, and low capacity for learning (Battin, ; Hale, Treml, & Swearer, ), and recent work has begun to explore taxonomic variability in the likelihood that closely related animals (e.g., different insect families) are susceptible to ecological traps (Robertson et al, ,).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations